Perancangan Helm Anak-anak yang Ergonomis (Studi Kasus di TK An-Namiroh Pekanbaru) - Merry Siska; Henedi Henedi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
AbstractThe comfort of the children is one of the important factor that must be considered by parents, especially when travel using a motorcycle. One of the equipment when using the motorcycle is helmet. Helmets that don’t have the ergonomics aspect will cause fatigue in it’s users. Therefore this study aims to redesign  the ergonomic helmet for the children. The design will be displayed in the form of 3D image and prototype. The first step in this research is collecting data. The data collected is anthropometric data children's heads as much as 80 students from kindergarten An-Namiroh. Anthropometric data that is needed are a high head, head width, head length, circle head, eyes to the head, and ears onto the head. The next step is anthropometric data processing which includes testing the normality of the data, testing the uniformity of data, testing the adequacy of the data, the calculation of percentiles, testing product concepts and drawings from the design. The last step is an analysis of the design product. Based on the results obtained helmet = 13 cm wide, circular helmet = 52.08 cm = 15,334 cm tall helmet, part of the helmet ear distance = 14.62 cm, length = 14.92 cm helmets, helmet glass distance to the eye is divided into 2 parts: a clear glass helmet = 4.85 cm, glass, black helmet = 5.72 cm.  Key words: Anthropometry, Ergonomics, Helmet  children